Effect of Excess Moisture and Shallow Ground Water Table on Growth, Yield and Heat Use Efficiency of Gram - Maurya, B.M; Sharma, R.K.; Yadav, R.D. (Journal of Soil and Water Conservation, 2022)
The experiment on effect of excess moisture and shallow ground water table on growth, yield and heat use efficiency of gram (Cicer arietinum L. ) was conducted at Zonal Agricultural Research Station Powarkheda during rabi season of 1992-93 and 1993-94 on clayey soil. The yield reduction due to 1-4 days submergence varied significantly. The gram crop tolerated, 1 day submergence effectively at sowing and pod development stage. The flowering stage was most sensitive stage for water logging. The drainage condition was excellent in well No. 1 and 7 at Baikhedi village. The average yield of gram Ujjain 21 varied from 16.4 q/ha to 18.75 q/ha. The yield reduction was 17.75% under fair drainage condition where water table was below 1 in from ground surface, 34.66% under poor drainage condition where the existing ground water table was 50- 100 cm from ground surface and 67.18% under very poor drainage condition where water table was within 50 cm from ground surface during crop growth period.